The Main Targets of Okadaic Acid Toxin in Human Intestinal Caco-2 Cells: An Investigation of Biological Systems - M Robati, Reza; Razzaghi, Zahra; Arjmand, Babak; Rezaei Tavirani, Mostafa; Rostami Nejad, Mohammad; Rezaei, Mitra; Zamanian Azodi, Mona (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: Okadaic acid (OA) is a toxin of polluted shellfish. Consuming the contaminated shellfish is accompanied by diarrhea and paralytic and amnesic disorders. There is a correlation between diarrhea and the consumed OA. Determining the critical targeted genes by OA was the aim of this study. Methods: The transcriptomic data about the effect of OA on human intestinal caco-2 cells were extracted from gene expression omnibus (GEO) and evaluated via the GEO2R program. The significant differentially expressed genes (DEGs) were included in a protein-protein interaction (PPI) network and the central nodes were enriched via gene ontology to find the crucial affected biological terms. Results: Among the 178 significant DEGs plus 50 added first neighbors, four hub-bottleneck genes (ALB, FOS, JUN, and MYC) were determined. Twenty-eight critical biological terms were identified as the dysregulated individuals in response to the presence of OA. “ERK1/2-activator protein-1 (AP-1) complex binds KDM6B promoter” was highlighted as the major class of biological terms. Conclusion: It can be concluded that down-regulation of ALB as a potent central gene leads to impairment of blood homeostasis in the presence of OA. Up-regulation of the other three central genes (JUN, FOS, and MYC) grossly affects the vital pathways in the human body.